2020
DOI: 10.1007/s40502-020-00541-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought length on the performance of cabbage (Brassica oleracea var capitata) in the forest-savannah transition zone, Ghana

Abstract: The drought tolerance of Cabbage, Brassica oleracea var capitata (Oxylus) was investigated by subjecting the initial, development and mid growth stages to varying drought lengths of 5, 7, 9, 11, 13 and 15 days in a 7 × 3 factorial experiment to determine the effect of each drought period at each growth stage on growth and yield. Data on number of opened leaves/plant, leaf area index (LAI), leaf chlorophyll content, head size and yield/ha were recorded due to drought effect at each growth stage. Analysis of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The influence of drought length on Brassica oleracea var. capitata seedlings was investigated in the forest-savannah transition zone in Ghana on a morphological and physiological level, without insight into photosynthesis [56]. The impact of water deficit on photosynthetic performance and growth was explored in aeroponically grown Tuscan kale (Brassica oleracea) in a tropical greenhouse [57] and also in juvenile Chinese kale (Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of drought length on Brassica oleracea var. capitata seedlings was investigated in the forest-savannah transition zone in Ghana on a morphological and physiological level, without insight into photosynthesis [56]. The impact of water deficit on photosynthetic performance and growth was explored in aeroponically grown Tuscan kale (Brassica oleracea) in a tropical greenhouse [57] and also in juvenile Chinese kale (Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%
“…Limited water availability at the initial stage ceased leaf formation and reduced the leaf number of brassica species [25]. Halted growth of leaf area under water stress conditions was due to a reduction in the total number of cells as mitotic activity of the epidermal cells decreased [26].…”
Section: Cultivation System Growth and Spad Valuementioning
confidence: 99%
“…Some studies have revealed that water stress experienced during critical growth stages can lead to significant reduction of crop yields [1,2]. To get the enhanced yields the availability of moisture during flowering and pod filling stages more important [3]. Water stress during both flowering and podfilling stages may reduce the crop yields [4].…”
Section: Introductionmentioning
confidence: 99%